Estrategias de marketing para la comercialización de los productos artesanales de la asociación de productores artesanales La Victoria ( APAV), parroquia La Victoria del cantón Pujilí. - Egas Vaca, Jessy Marianela (2020)
In the case of study carried out, an analysis is proposed that allows giving a social and family organization such as the APAV a marketing vision oriented to the Marketing of its artisan products, based on the situational analysis where a series of administrative and administrative elements are established. Operations that are limiting development and growth in terms of sales. The study is mainly focused on determining a research methodology with a qualitative approach where it is deepened through an exploratory research level and the application of interviews directed to the Board of Directors of the Association, reaching to investigate the critical factors of the organization. Based on the elements found, a structured proposal is proposed in conceptual marketing models for the approach of marketing strategies where brand design, packaging and distribution channels are integrated, allowing better the image of the product to the target audience. The research work complies with the presentation of a modern and updated marketing structure that adapts to the changes demanded by the market, giving the product a more competitive vision in the face of the conditions demanded by the current market.